Pandemi Covid-19 dan Ekspresi Beragama: Studi Pelaksanaan Majelis Taklim di Kota Banjarmasin - Wahdini, Muhammad; Ariyadi, Ariyadi; Abdillah, Muhammad Torieq (The Sociology of Islam, 2022)
One of the efforts made by the government spread and stop the Covid-19 pandemic is to limit various community activities. The religious expression sector is also experiencing restrictions, religious activities must carry out standardization of health protocols. The Banjarmasin City Government has implemented PSBB and PPKM as a follow-up to the Central Government. This has serious consequences for the religious expression of the people of Banjarmasin, which is dominated by Muslims and has an active and high religious culture. Expressions of diversity such as the majelis taklim for the people of Banjarmasin City are like a culture that is taboo to be eliminated, so there is a contradiction between the Covid-19 pandemic and religious expressions that are carried out. This study aims to determine the compatibility between das sollen and das sein and to find out the effectiveness of the implementation of Banjarmasin City Government policies in efforts to handle Covid-19, especially in the sector of limiting religious expression. The method used is an approach that can be chosen and used by researchers, namely a qualitative approach. The findings of this study are the fact that the Banjarmasin City Government Policy when issuing PSBB and PPKM instructions tends to be obeyed by majelis taklim managers, but after the PSBB and PPKM are finished even though the Covid-19 pandemic is still ongoing, majelis taklim in Banjarmasin City continues and some findings are still there. Majelis taklim that does not meet strict health protocol standards.